Makna Syifa dalam al-Qur’an (Analisis Semiotika Roland Barthes pada QS al-Isra 82) - Roma Wijaya (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
This paper examines the meaning of shifa in the Qur'an as stated in Q.S. Al-Israa [17]: 82 which can be used as a means of treating various diseases, both psychological and physical. Employing the semiotic theory of Roland Barthes consisting of two stages (the linguistic system which is also interpreted as denotative meaning and the system of mythology (myth) as connotative meaning), the results obtained that shifa is not only oriented to the psychic alone, but to healing both the psychic (spiritual) and physical. The message contained in the verse is that it is recommended to do treatment using the Qur'an, with lawful (halal) practices, and it is not allowed to practice medical treatment that can classify to shirk such as using magic spells, mediation of belief in objects, sacred places of worship, and other things that are superstitious. Tulisan ini mengkaji tentang makna syifa dalam Al-Qur'an sebagaimana tertuang dalam Q.S. Al-Israa [17]: 82 yang dapat digunakan sebagai sarana pengobatan berbagai penyakit, baik psikis maupun fisik. Dengan menggunakan teori semiotika Roland Barthes yang terdiri dari dua tahap (sistem linguistik yang juga diartikan sebagai makna denotatif dan sistem mitologi (mitos) sebagai makna konotatif), diperoleh hasil bahwa syifa tidak hanya berorientasi pada psikis saja, tetapi untuk penyembuhan baik psikis (spiritual) maupun fisik. Pesan yang terkandung dalam ayat tersebut adalah dianjurkan untuk melakukan pengobatan dengan menggunakan Al-Qur'an, dengan praktik yang halal dan tidak diperbolehkan melakukan praktik pengobatan yang dapat digolongkan ke dalam syirik seperti menggunakan mantra sihir, perantaraan benda-benda, tempat-tempat ibadah yang keramat, dan hal-hal lain yang bersifat takhayul.